Investigation of the dynamic charge transport behaviours under electron beam irradiation of advanced insulation materials for aerospace applications - Guangyu Sun; Xiong Yang; Wentong An; Kun Huang; Xiaogang Qin; Baipeng Song; Guanjun Zhang (High Voltage)
Abstract Aerospace dielectric components on spacecrafts are frequently exposed to surface charging. Here the dynamic charging behaviours of advanced aerospace dielectrics under electron beam irradiation are investigated. Combined measurement of dielectric secondary emission yield (SEY) and trap distribution provides input parameters of a drift‐diffusion transport model reproducing the beam‐irradiated dielectric charging processes. The model reveals the spatial–temporal evolutions of the current, charge density, and electric field distribution. The model‐predicted sample current, SEY and surface potential, in a surface layer of 1 μm and with incident electron energy range of 10–30 keV, are compared with the experiments, showing qualitative agreement. The effects of beam energy and current, dielectric material, and sample thickness on the charging processes are explored. Relation between the beam energy and final surface potential is determined, and the beam current is found to only affect the charging speed. Dielectric parameters including the mass density, permittivity, surface resistivity, trap state distribution, electron affinity, together influence the charging speed and final charged state.